Analyzing differences between spatial exposure estimation methods: A case study of outdoor food and beverage advertising in London, Canada. (January 2023) - Wray, Alexander; Martin, Gina; Doherty, Sean; Gilliland, Jason
Abstract: Exposure assessment in the context of mobility-oriented health research often is challenged by the type of spatial measurement technique used to estimate exposures to environmental features. The purpose of this study is to compare smartphone global positioning system (GPS), shortest network path mobility, and buffer-based approaches in estimating exposure to outdoor food and beverage advertising among a sample of 154 teenagers involved in the SmartAPPetite study during 2018 in London, Ontario, Canada. Participants were asked to report their home postal code, age, gender identity, ethnicity, and number of purchases they had made at a retail food outlet in the past month. During the same time period, a mobile phone application was used to log their mobility and specifically record when a participant was in close proximity to outdoor advertising. The results of negative binomial regression modelling reveal significant differences in estimates of advertising exposure, and the relationship to self-reported purchasing. Spatial exposure estimation methods showed differences across regression models, with the buffer and observed GPS approaches delivering the best fitting models, depending on the type of retail food outlet. There is a clear need for more robust research of spatial exposure measurement techniques in the context of mobility and food (information) environment research. Highlights: Exposure to outdoor food and beverage advertising has little association with purchasing among adolescents. Comparison of GPS, network paths, and residential buffers in measuring exposure to outdoor food and beverage advertising. Residential buffers and GPS delivered the best-fitting models, dependent on the type of retail food outlet under study.